Five-factor model personality traits, exclusive breastfeeding, and self-efficacy: a mediational analysis - Parvin Yadollahi; Fatemeh Padashian; Marziyeh Doostfatemeh (BMC, 2024)
Abstract Background Despite the World Health Organization's (WHO) emphasis on exclusive breastfeeding, the documents show a declining trend worldwide. Studies assert that the mother's personality traits appear to have an impact on this issue. This study aimed to investigate the potential influence of personality traits on exclusive breastfeeding, which might be channeled by self-efficacy as a mediator variable. Methods Data were analyzed from the cross-sectional study. The exclusive breastfeeding scale, the breastfeeding self-efficacy questionnaire, and the Five-Factor Model questionnaire (as follows: neuroticism, extraversion, openness experience, agreeableness, and conscientiousness) were completed by120 Iranian volunteer mothers with an infant aged 6-12 months referred to health centers in Shiraz (a major city in southern Iran) between May to December 2019. The structural equation modeling (SEM) approach was used to obtain the direct and indirect effects of personality traits and self-efficacy on exclusive breastfeeding. Results The study showed the significant direct effect of some personality traits (agreeableness, extraversion, and consciousness) and self-efficacy on exclusive breastfeeding. The indirect effect of extraversion on exclusive breastfeeding through self-efficacy was also obtained from the result of SEM analysis. The model fit the data satisfactorily, according to the fit indices criteria extracted from the mediational analysis. Conclusions Self-efficacy appears to be a significant predictor of exclusive breastfeeding. Therefore, exclusive breastfeeding could be enhanced by safe education in pregnancy, reinforcing the self-efficacy of pregnant women and considering their personality traits.